An easy and widely applicable forecast control for heating systems in existing and new buildings: First field experiences. (10th June 2022) - Cholewa, Tomasz; Siuta-Olcha, Alicja; Smolarz, Andrzej; Muryjas, Piotr; Wolszczak, Piotr; Guz, Łukasz; Bocian, Martyna; Balaras, Constantinos A.
Abstract: An accurate prediction and regulation of the energy supplied to the buildings can increase the energy efficiency of existing and new buildings. However, there is no low cost, easy to install and operate system and a simple method for the forecast control of a heating system dedicated to existing buildings. This work elaborates the first experiences from the installation, operation and maintenance of the proposed forecast control system in a multi-family building and an office building located in Poland. The method takes into account the building's actual energy model and the installed heating system (in the form of an equivalent outdoor temperature), the user behavior and preference profiles (in the form of an equivalent indoor temperature) and the forecast of weather parameters. Actual energy savings resulting from the use of this forecast control system in the two monitored buildings averaged over 15%. The installation of this system in existing buildings requires less than 2 h and it does not impose any difficulties for users or facility managers. Highlights: New forecast control of a central heating hydronic system. First experiences from the installation, operation and maintenance. Installation time requirements are less than 2 h. Widely applicable measure for obtaining energy savings.